Rheumatologic skills development: what are the needs of internal medicine residents?. Issue 8 (August 2016) - Kroop, Susan; Chung, Cecilia; Davidson, Mario; Horn, Leora; Damp, Julie; Dewey, Charlene
Abstract Given the burden of rheumatic disease in our society and the anticipated future shortage of rheumatologists, all internal medicine (IM) residencies need to train internists who are capable of caring for patients with rheumatic diseases. The objective of this study was to perform a targeted needs assessment of the self-confidence of IM residents in the evaluation and care of patients with rheumatologic diseases. A 16-item, web-based, self-assessed confidence survey tool was administered to participating post graduate year (PGY)1 (N = 83) and PGY3 (N = 37) residents. The categories of questions included self-confidence in performing a rheumatologic history and exam, performing common rheumatologic procedures, ordering and interpreting rheumatologic laboratory tests, and caring for patients with common rheumatologic diseases. Resident demographics, prior rheumatology exposure, and career plans were also queried. PGY3 residents had higher self-assessed confidence than PGY1 residents in all categories. Self-assessed confidence in joint procedures was consistently low in both groups and when compared to other categories. Prior exposure to a rheumatology course or elective was not consistently associated with higher self-assessed confidence ratings across all categories. PGY3 residents showed less interest in rheumatology as a career than PGY1 residents, although the interest in the topic of rheumatology was not statistically different. Our needs assessment shows a low level of self-assessed confidence in rheumatology knowledge and skills among IM residents. Despite improvement with PGY year of training, self-assessed confidence remains low. To improve resident's skills and self-confidence in rheumatology, more curricular innovations are needed. Such innovations should be assessed for overall effectiveness.